1997
DOI: 10.1007/bf00390052
|View full text |Cite
|
Sign up to set email alerts
|

Tibial avulsion fracture of the posterior cruciate ligament: K-wire or screw fixation?

Abstract: Although the posterior cruciate ligament (PCL) is not frequently injured, a greater understanding of its role in stabilizing the knee joint, mechanism of injury and treatment has developed. Isolated avulsion injuries constitute only a subgroup of PCL injuries, but nevertheless several operative techniques have been described for the fixation of the avulsed bony fragment. In order to investigate whether K-wire or screw fixation yields better long-term results, we examined 26 patients at an average of 10.5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…In adults, injuries to the PCL typically are limited to the substance of the ligament [30]. Bony avulsions, in which an osteochondral fragment is detached from the PCL insertion site, also have been reported in adults [5,8,11,17,22,23,29,33,35,39]. In the pediatric population, PCL injuries are rare, likely as a result of the elasticity of the ligament [9,10,28].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, injuries to the PCL typically are limited to the substance of the ligament [30]. Bony avulsions, in which an osteochondral fragment is detached from the PCL insertion site, also have been reported in adults [5,8,11,17,22,23,29,33,35,39]. In the pediatric population, PCL injuries are rare, likely as a result of the elasticity of the ligament [9,10,28].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on 36 patients with bone avulsion of the PCL in its tibial insertion, Torisu (8) found that the injury was secondary to a motorcycle accident in 47% of the cases, and identified the presence of the injury on the anterior tibial surface in 47% of the patients. Seitz et al (10) retrospectively assessed 26 patients and found a similar mechanism of injury in 87% of the cases, and injury on the anterior leg surface in 100%. In our case series, 57% of the injuries were resultant from motorcycle accidents, and 17% have been caused by car accidents, while the presence of injury on the anterior leg surface was found in 62% of the cases.…”
Section: Discussionmentioning
confidence: 96%
“…Torisu (9) assessed 21 patients with avulsion fracture of the tibial insertion of PCL, affecting males in 76% of the cases. Seitz et al (10) in a retrospective study with 26 patients, reported 73% of male cases, with a mean age of 23 years. In this study, patients' ages ranged from 15 to 53 years (mean = 29 years), and 76% were males.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations